Jezik podobe in podoba jezika - Ženko, Ernest (Šolsko polje, 2006)
The article deals with the relationship between the discursive and the pictorial, which is expressed in philosophy and theory in the second half of the 20th century as a shift from the linguistic turn (Rorty) to the pictorial turn (Mitchell) but which at the empirical level appears as the primacy of theworld of fixed and moving images. In the 1930s the multifaceted artist and teacher László Moholy-Nagy declared that the illiterate of the future would be'the man who cannot take a photograph'. It appears that the future he had inmind is already part of the age we live in, although the unusual thing here is that at the level of everyday life we are clearly already aware of this process, since we attribute an extraordinary role and power to images. Unfortunately this is not the case in education, as is demonstrated by a simple look at primary and secondary school curricula, where for example in the final year of nine-year primary education almost ten times as many hours are dedicated to languages as to art education. The author further establishesthat the views of some teachers who claim that the omnipresence of images today is already threatening language, literature and reading are exaggerated and inappropriate, since in the name of the protection of language they advocate a form of education that is one-sided and does not enable the understanding and interpretation of images. In this way they do notallow the balanced education of new generations but instead force them intonew, more contemporary forms of illiteracy.
Keywords: literacy; pismenost; filozofija jezika; jezikovni obrat